بصيرة اللغة: نظرة براجماتية Book Chapter ” حان وقت حرية التعلم “ تأليف نينو إندريانتو والأصدقاء - Dina Putri Juni Astuti; Ikke Wulandari (UIN Fatmawati Sukarno Bengkulu, 2021)
Language wisdom is a language unit selection strategy that is used to become a filter in dealing with language communication in terms of pragmatics in the digital era 4.0. The strategy for selecting language units in this study is based on the classification of speech acts and the principles of politeness in language used in vocabulary in the book chapter “Time for Freedom to Learn” by Nino Indrianto et al. The research method used is descriptive method with data collection techniques using library research techniques. Where the research data is in the form of sentences related to language wisdom with a pragmatic review of the book chapter